Mandatory Severance Pay : Its Coverage and Effects in Peru - MacIsaac, Donna (World Bank, Washington, DC, 2014)
In Peru, as in many other developing countries, employers have the legal obligation to compensate workers who are dismissed through no fault of their own. Is this an efficient mechanism for providing income support to the unemployed? The authors seek an answer to this question, using individual records from a household survey with a panel structure. Relying on five coverage indicators, they show that roughly one in five workers in the private sector, and one in three wage earners in the private sector, is legally entitled to severance pay. Coverage is more prevalent among wealthier workers. Results based on several empirical strategies suggest that workers "pay" for their entitlement to severance pay through lower wages. Consumption among unemployed workers who receive severance pay is 20 to 30 percent greater than among those who do not. Consumption among these workers is actually higher than consumption among employed workers, suggesting that mandatory severance pay is overgenerous in Peru.